Data Security Analysis in Information Management in Digital Food Sovereignty Systems - Putri Amaranggani, Ida Ayu Dara; Lilik Widyawati; Dadang Priyanto; Galih Hendro Martono, (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The digital food sovereignty system represents an innovation in food information management, enhancing efficiency, transparency, and food security across various sectors. However, during its implementation, data security remains one of the most significant challenges that must be addressed to ensure the system’s continuity and reliability. This study aims to analyze data security aspects within the digital food sovereignty system, focusing on potential risks, vulnerabilities, and applicable mitigation strategies. A descriptive qualitative approach was employed, involving data collection through direct observation, stakeholder interviews, and literature reviews from relevant sources. The findings indicate that key challenges in data security include threats from cyberattacks, data breaches, and insufficient user awareness regarding the importance of information protection. To address these issues, strict security measures such as data encryption, multi-layered authentication, and regular system monitoring are essential. The analysis highlights that strengthening data security in digital food sovereignty systems requires a comprehensive approach that integrates technical solutions, policy development, and user education. This research is expected to contribute to the formulation of more effective security strategies that support the advancement of digital-based food sovereignty.